Editorial on Totally endoscopic (VATS) first rib resection for thoracic outlet syndrome - Kara, H. Volkan (Journal of Thoracic Disease, 2017)
Thoracic outlet syndrome (TOS) is defined as compression of neural and vascular structures passing through the superior aperture of the chest ‘Thoracic Outlet’. The involved anatomical structures are brachial plexus, subclavian artery and vein, and they are at risk of compression on their course between neck and axilla.